1999
DOI: 10.1162/089892999563391
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Brain Activity during Visual Imagery of Letters

Abstract: Cortical signals associated with visual imagery of letters were recorded from 10 healthy adults with a whole-scalp 122-channel neuromagnetometer. The auditory stimulus sequence consisted of 20 different phonemes corresponding to single letters of the Roman alphabet and of tone pips (17%), delivered once every 1.5 sec in a random order. The subjects were instructed to visually imagine the letter corresponding to the auditory stimulus and to examine its visuospatial properties: The associated brain activity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…4). This finding is in line with those of Raij (1999) and Sakowitz et al (2001), according to whom cortical activation following audio-visual stimuli involves the activation of multiple cortical regions. Also, it was shown that even simple visual stimuli activate a large number of distinct occipital, temporal, and parietal cortical areas (Felleman and Van Essen 1991).…”
Section: Beta Oscillationssupporting
confidence: 91%
“…4). This finding is in line with those of Raij (1999) and Sakowitz et al (2001), according to whom cortical activation following audio-visual stimuli involves the activation of multiple cortical regions. Also, it was shown that even simple visual stimuli activate a large number of distinct occipital, temporal, and parietal cortical areas (Felleman and Van Essen 1991).…”
Section: Beta Oscillationssupporting
confidence: 91%
“…The precuneus has been implicated in various functions including visuo-spatial imagery and memory retrieval (for a review see Cavanna and Trimble, 2006). The left precuneus has been implicated in visual imagery of letters, specifically the visuo-spatial aspects of the imagery (Raij, 1999). Thompson et al (2009) found bilateral precuneus activation during a spatial location task compared to a spatial-transformation task.…”
Section: Discussionmentioning
confidence: 99%
“…, [68]) and auditory [8][10] spatial attention tasks. As suggested by non-human primate neurophysiological [69] as well as human fMRI [70], [71] and MEG [72] studies, the precuneus is central for complex spatial processes that require combining information from different modalities and spatial frames of references. Such processes include navigation [70], [71], updating object-position information during observer motion [73], and linking motor goals to visuospatial representations [74], [75].…”
Section: Discussionmentioning
confidence: 99%